Atari : between a rock and a hard place - Shein, James B., 1942- (SAGE knowledge. Cases., 2016)
Atari, a maker of video games, went through several owners over the years, winding up controlled by Infogrames, a French publisher of video games. Infogrames later sold Atari shares in a secondary public offering, eventually reducing the parent's share to 51.6 percent by September 2005 and creating a complicated two-tier ownership structure. This study examines the multiple challenges which were faced by Atari's management.